High frequency CNTFET-based logic gate - Farhana, Soheli; Alam, A. H. M. Zahirul; Khan, Sheroz (2015)
Modeling of high frequency carbon nanotube field effect transistor (CNTFET) is analyzed in this paper to develop logic gate. The aim of this research is to minimize the dimension of the logic gate for the future electronic device application. The analytical models of CNTFETs are employed to model the logic gates and verify their transfer characteristics. The logic gates discussed in this paper are inverters, NOR gate and NAND gate. The high frequency response is achieved from the proposed logic gates operation analyzed from the small signal model. Finally the results show the electronic properties of carbon nanotubes (CNTs) affect the variations for the logic gate’s transfer characteristics.